ANALISIS FEMINISME NOVEL THE PRINCESS SULTANA’S DAUGHTER KARYA BESTELLER PRINCESS - Erlina, Erlina (Ensiklopedia of Journal, 2022)
This research is motivated by the analysis of feminist novel The Princess Sultana's Daughter by Besteller Princess. Feminist is a movement of women to reject everything that is marginalized, subordinated and demeaned by the dominant culture, both in the political, economic and social life in general. This study aimed to describe the feminist movement in The Princess Sultana's Daughter novel. The research is a qualitative study using descriptive methods. The object of this research is The Princes Sultana's Daughter novel by Besteller Princess. Data collection techniques in this study are: First, read, understand novel The Princes Sultana's Daughter. Secondly, carry out studies related to the research literature. Third, note the data associated with feminism. While the steps in analyzing data are: (1) read and understand the novel The Princes Sultana's Daughter overall, (2) identify feminism contained in the novel The Princes Sultana's Daughter, (3) classifies the data, (4) analyze the data that has been classified, (5) interpret and describe data, (6) take the conclusions from the results of the analysis, and (7) make research report in the form of a thesis. The results of this study stated that this novel tells a lot about the tragic story of the women of Saudi Arabia and Sultana's daughter struggle demanding equal rights of women with men. Daughter demanded that the similarity in genre.Keywords: feminism, novel.